The General Election Supervisory Agency (Bawaslu) Role In Preventing 2024 Election Violations - arja, arja (GoResearch - Research & Publishing House, 2023)
The purpose of this study is to understand the role of Bawaslu in preventing election violations in 2024. The approach in this study is qualitative using the literature study method (library reseach) focuses on reviewing various literatures. This method involves collecting data sources namely; books, journals, academic research, and other sources relevant to this research. The results of this study show that;First, Bawaslu has extraordinary authority as an election supervisory institution, including as the executor and adjudicator of cases of election violations. Second,In an effort to increase the effectiveness of supervision and prevention of election violations, Bawaslu needs to take corrective steps. This includes improving quality systems and human resources, reforming the bureaucracy, increasing cooperation with related institutions, and increasing community participation.Third, by making the necessary improvements and improvements, Bawaslu can play a more effective role in realizing elections with integrity, fairness and free from violations.